The arrangements of online dispute resolution as an alternative resolution of the electronic commerce transactions in Indonesia - Tektona, Rahmadi Indra; Rachmawati, Ayudya Rizqi (Penerbit Universiti Kebangsaan Malaysia, 2020)
The article is motivated by the practical preference from conventional alternative dispute resolution to online dispute resolution as information and communication technology progresses, especially in electronic commerce. It aims to provide a concept about the fore on regulations of online dispute resolution as an alternative dispute resolution applicable to electronic commerce in Indonesia. This normative legal research which uses statute and comparative approach provides an explanation on the importance of regulating online dispute resolution so as to give legal certainty and legal protection to consumers of electronic commerce.